PERBEDAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENTS DIVISONS (STAD) DENGAN TIPE NUMBER HEAD TOGETHERS (NHT) TERHADAP MOTIVASI DAN HASIL BELAJAR KIMIA SISWA KELAS XII SMK NEGERI 2 MANOKWARI - Wutoy, Regina A.; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2015)
This study aims to Know (1) differences STAD cooperative learning model with NHT on motivation to learn chemistry in Class XII TKJ A and B, SMK Negeri 2 Manokwari (2) differences STAD cooperative learning model with NHT to the learning outcomes of Chemistry in TKJ XII Class A and B, SMK Negeri 2 Manokwari. (3) the effect of cooperative learning model tipeStudent Team Achievement Devision (STAD) and NHT on learning outcomes of Chemistry Class XII TKJ A and B, SMK 2. The design used was a type of non-equivalent pretest-posttest design. The results showed that: (1) There are differences in the application of the model of cooperative STAD pembelajran NHT premises on motivation to learn chemistry class XII student of SMK Negeri 2 Manokwari. This is evidenced by the results of the analysis are obtained, the Sig (2-tailed) research is smaller than 0.05 0.001 (2) There is a difference in the application of cooperative learning model type STAD with NHT on learning outcomes chemistry class XII student of SMK Negeri 2 Manokwari. This is evidenced by the results of the analysis, the Sig (2-tailed) research is 0.001 less than 0.05 (3) There is a learning outcome chemistry taught by the application of cooperative learning model type STAD with NHT in Class XII student of SMK 2 Manokwari country. Keywords: Cooperative Learning Model STAD and NHT, Motivation, Learning Outcomes